Dysregulation of PINCH signaling in mesial temporal epilepsy. (February 2017) - Liu, Charles; Russin, Jon; Heck, Christianne; Kawata, Keisuke; Adiga, Radhika; Yen, William; Lambert, Jonathan; Stear, Benjamin; Law, Meng; Marquez, Yvette; Crino, Peter; Millett, David; et al.
Highlights: PINCH and hpTau are expressed in mesial temporal epilepsy. Data point to AKT/GSK3β signaling dysregulation in hpTau formation in MTLE. Dissecting the role of PINCH in MTLE will increase understanding mechanisms in MTLE. Abstract: Mounting evidence suggests that inflammation is important in epileptogenesis. P articularly I nteresting N ew C ysteine H istidine-rich (PINCH) protein is a highly conserved, LIM-domain protein known to interact with hyperphosphorylated Tau. We assessed PINCH expression in resected epileptogenic human hippocampi and further explored the relationships among PINCH, hpTau and associated kinases. Resected hippocampal tissue from 7 patients with mesial temporal lobe epilepsy (MTLE) was assessed by Western analyses to measure levels of PINCH and hyperphosphorylated Tau, as well as changes in phosphorylation levels of associated kinases AKT and GSK3β in comparison to normal control tissue. Immunolabeling was also conducted to evaluate PINCH and hpTau patterns of expression, co-localization and cell-type specific expression. Hippocampal PINCH was increased by 2.6 fold in the epilepsy cases over controls and hpTau was increased 10 fold over control. Decreased phospho-AKT and phospho-GSK3β in epilepsy tissue suggested involvement of this pathway in MTLE. PINCH and hpTau co-localized in some neurons in MTLE tissue. While PINCH was expressed by both neurons and astrocytes in MTLE tissue, hpTau was extracellular or associated with neurons. PINCH was absent from the serum of control subjects but readily detectable from the serum of patients with chronic epilepsy. Our study describes the expression of PINCH and points to AKT/GSK3β signaling dysregulation as a possible pathway in hpTau formation in MTLE. In view of the interactions between hpTau and PINCH, understanding the role of PINCH in MTLE may provide increased understanding of mechanisms leading to inflammation and MTLE epileptogenesis and a potential biomarker for drug-resistant epilepsy.